Multi-response biocompatible Janus micromotor for ultrasonic imaging contrast enhancement. (June 2021) - Feng, Yiwen; Chang, Xiaocong; Liu, Hao; Hu, Ying; Li, Tianlong; Li, Longqiu
Highlights: A new Janus micromotor with multiple responses (ultrasonic, magnetic field, and chemical stimuli) is proposed. Swarm intelligent targeted drive control of the micromotors is realized. Contrast-enhanced effect of the micromotors as an ultrasonic contrast agent is observed. Abstract: The acid-base environment of the biological digestive system is formed with the help of hydrogen ions and bicarbonate. At the same time, the chloride capacity in the blood is not ignorable. These ionic environments provide a new horizon for the medical application of bubble-propelled micromotors. Herein, a Janus Mg-based micromotor is reported as a novel ultrasonic contrast agent and its potential advantages in medical imaging are explored. With the capability of being powered by the magnetic field, these micromotors could be navigated to the corresponding ionic environment, and then they would rapidly generate continuous bubbles. These bubbles achieve an efficient and guided propulsion of micromotor, also provide support for contrast-enhanced ultrasound imaging. Besides owning the dual functions of imaging and targeted transport, the micromotors present aggregation response under the action of ultrasound, which is helpful for local reinforcement of the imaging effect. Such multi-response biocompatible Janus micromotor provides a new perspective for medical imaging and diagnosis. Graphical abstract: Image, graphical abstract